International Migration As A Driver Of Country Development - Denys Pudryk (SocioEconomic Challenges)
The expression of the country’s sustainable socio-political development is its achievement of macroeconomic stability, which, first of all, depends on the ability of the national economy to ensure the growth of macroeconomic indicators. It raises many questions about identifying and evaluating factors that directly and indirectly impact growth. In recent decades, more and more attention is paid to the problems of developed countries’ human capital security and their importance for macroeconomic processes. Human resources can be interpreted as explicit (labor resources) and implicit (ethnic, age, language, qualification distribution, etc.) factor influencing macroeconomic indicators. Since most economically advanced states belong to the category of old nations, they have faced another global problem in the last half-century – the population’s rapid ageing. Their gradual degeneration leads to the inhibition of positive macroeconomic processes. Therefore there is a need to attract new human resources, and migration is one of the most effective levers to solve this problem. However, migration can pose several threats to both the destination country and the donor country. In the economic context for the destination country, the most serious of these is the lack of the desired improvement in human potential due to the influx of low-skilled workers. In contrast, for the country of origin, there is a brain drain. It creates the problem of determining the factors that affect population migration between the donor country and the destination country, and their correlation with macroeconomic indicators. The purpose of this work is to conduct a generalized analysis of methodologies for assessing the interconnectedness of macroeconomic and migration determinants and identifying commonalities. According to the work results, it was found that most of the analyzed scientists use simple estimation models, filling them with related indirect migration factors and macroeconomic indicators, which are formed depending on the primary goal of the work. Thus, this study allows us to create a list of migration determinants commonly used in typical results, to form an updated methodological framework.